2012
DOI: 10.1227/neu.0b013e31823f6571
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Catheter Location and the Clearance of Intraventricular Hemorrhage

Abstract: Background There is no consensus regarding optimal position of external ventricular drain (EVD) with regard to clearance of intraventricular hemorrhage (IVH). Objective To assess the hypothesis that EVD laterality may influence the clearance of blood from the ventricular system, with and without administration of thrombolytic agent. Methods The EVD location was assessed in 100 patients in two CLEAR Phase II trials assessing the safety, and dose optimization of thrombolysis through the EVD to accelerate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 13 publications
4
10
0
5
Order By: Relevance
“…Webb et al [21] observed a faster reduction in IVH score (clearance to 50%) in all assessed regions with increasing rtPA dose. The influence of location of EVD on clot resolution in CLEAR-IVH was assessed by Jaffe et al [29]. Those findings confirm some aspects reported in a recently published nonrandomized study, which compared between a dosing of 1 mg rtPA every 8 h (n ¼ 22) and 4 mg rtPA every 12 h (n ¼ 32) in a cohort of patients selected by similar inclusion criteria, as in CLEAR-IVH [28].…”
Section: Introductionsupporting
confidence: 67%
“…Webb et al [21] observed a faster reduction in IVH score (clearance to 50%) in all assessed regions with increasing rtPA dose. The influence of location of EVD on clot resolution in CLEAR-IVH was assessed by Jaffe et al [29]. Those findings confirm some aspects reported in a recently published nonrandomized study, which compared between a dosing of 1 mg rtPA every 8 h (n ¼ 22) and 4 mg rtPA every 12 h (n ¼ 32) in a cohort of patients selected by similar inclusion criteria, as in CLEAR-IVH [28].…”
Section: Introductionsupporting
confidence: 67%
“…‘Ipsilateral’ or ‘contralateral’ ventricles were defined relative to catheter-associated rtPA administration, as the impact of IVH and ICH laterality has been reported elsewhere. 10 AW, SM and NU independently scored CLEAR-IVH: Safety scans, whilst CLEAR-IVH: Dose-Finding scans were scored by AW and DH. ‘Stability’ CT was the first scan with no catheter-tract hemorrhage or ICH growth >5cc.…”
Section: Methodsmentioning
confidence: 99%
“…Associations between HU quantification and change in IVH volumes reflect the most accurate assessment methods available but may have been affected by disparities in sampling, patient age, and time of EVD placement. Numerous factors have been shown to influence clearance rates of intraventricular blood after rtPA administration, including the location of the external ventricular drain, 16 bilateral-versus-single EVD, 17 the location of intraventricular blood, dose of thrombolytic, 18 and serum and CSF components. Our investigation examined the radiographic characteristics that complement these data.…”
Section: Discussionmentioning
confidence: 99%